Roman Law as Ius Commune in East Central Europe: the Example of the Lands of the Crown of Saint Stephen - Petrak, Marko (Lectures on East Central European Legal History, 2023)
The aim of the chapter is to analyze the significance and role of Roman law as ius commune in East Central Europe (Ostmitteleuropa) from the Middle Ages up until today. The notion of East Central Europe will be pragmatically exemplified for the purposes of this contribution within the context of the Lands of the Crown of Saint Stephen. This territory was and is ‘the very heart’ of East Central Europe, as it comprises, in their entirety or partly, the following present-day states: Hungary, Croatia, Slovakia, Austria, Poland, Romania, Serbia, Slovenia, and Ukraine. The centrality and importance of the Lands of the Crown of Saint Stephen within East Central Europe also guarantee that the experience of Roman law as ius commune in these territories is not unimportant and has a certain level of paradigmaticity. The most important source of traditional pre-1848 law in the Lands of the Crown of Saint Stephen was undoubtedly the Tripartitum (1514), which represents one of the milestones of East Central Europe’s legal tradition and culture. Despite the explicit declaration that Roman law and canon law are the very basis of the law of Archiregnum Hungaricum (omnia fere iura regni huius originaliter ex pontificiis caesareique iuris fontibus progressum habeant), this legal collection was, in reality, a compilation of customary law and a powerful legal practice forming work that hindered any major legal transfer. Regardless of the fact that European ius commune was not a direct source of law in the pre-1848 period, there were definitely some ‘channels’ through which Roman legal tradition exerted a considerable influence and impact in the Lands of the Crown of Saint Stephen (e.g., procedural law manuals like Kitonich’s Directio Methodica and the inclusion of Digesta 50,17 in Corpus Iuris Hungarici), creating the phenomenon called tacita receptio. Only since the second half of the 19th century onward has Hungarian judicial practice and doctrine – due to the withering away of feudal relations and consecutive failed attempts to pass a modern national civil code – gradually elevated Roman private law in the form of ius commune to the level of a subsidiary source of law. The last part of the contribution deals with the role and significance of Roman law as ius commune in the former Lands of the Crown of Saint Stephen in the last hundred years, emphasizing that a possible wider scope of the application of the ius commune rules in the national judicial practice, especially in the form of regulae iuris, would not just represent a nostalgic quest for the hidden treasure of the European legal tradition but rather a part of a long-term creative effort toward the non-legislative Europeanization of the contemporary legal orders on the firm foundations of the common legal culture.KEYWORDS: Roman law, ius commune, East Central Europe, Lands of the Crown of Saint Stephen, Tripartitum, Corpus Iuris Civilis, Corpus Iuris Hungarici, legal tradition, legal maxims.